Ottoman apprentices and their experiences - Turna, Nalan (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
In this article, I analyze craft and trade apprentices in the late Ottoman Empire in order to add a new dimension to the existing literature on guilds and artisans. Rather than presenting an ideal picture, I discuss the apprentices' actions and experiences, which I argue did not take place in isolation.First, I briefly discuss Ottoman guilds and artisans, including a literature review, define and explain both the system of apprenticeship and who apprentices were.After focusing on the dialectical relationship between the upper and lower ranks, which presented itself through the authority - obedience or autonomy - disobedience relationship, I explain how the lower rank attempted to gain autonomy. I also question whether guild harmony was real or not and explore how some apprentices changed the direction of their life path, away from mastership to something else entirely. The hidden and unhidden resistance of apprentices will be shown through acts of theft, assault with a knife, and absconding, and through survival strategies which included running away. In the final part of the article, I describe how new institutions filled the gap left by the traditional guild system, which had been on the decline since the nineteenth century.
Keywords: apprentices; apprenticeship; ordinary people; craft and trade guilds; Ottoman Empire; urban history; Area Studies